FAKTOR – FAKTOR YANG MEMPENGARUHI KEJADIAN ANEMIA PADA IBU HAMIL DI BPM SRI WIDAYATNI SIDOHARJO WONOGIRI - Kristiningtyas, Y Wahyunti; Widayatni, Sri (Akademi Keperawatan Giri Satria Husada Wonogiri, 2020)
Anemia in pregnant women can cause labor complications, risk of shock during delivery, easy disease during pregnancy, miscarriage, premature birth, babies born with LBW, congenital abnormalities / fetal defects, and result in the maturity of fetal organ function imbalance. The frequency of pregnant women with anemia in Indonesia is relatively high, namely 63.5%. According to Riskesdas (2013) the prevalence of anemia in pregnant women is 36.4% in rural areas and 37.8% in urban areas. Data on the incidence of anemia in pregnancy in Central Java Province is 90.75%. The research objective was to analyze the factors that influence the incidence of anemia in pregnant women. This type of research is an analytic survey with a cross sectional approach. The population in this study were 76 pregnant women who visited BPM Sri Widayatni for ANC from May to June. The research sample was 76 pregnant women. The sampling technique uses total sampling. The research instrument used a questionnaire that had been tested for validity and reliability. Univariate, bivariate data analysis with chi square and multivariate logistic regression with multiple prediction models. The results showed that most of the respondents had advanced education (65.79%), most of the respondents had good knowledge (59.21%), most of the respondents with nutritional status were not KEK (60.53%) and most respondents had low economic status (60 , 53%). The incidence of anemia in pregnant women was 38 (50%). Independent variables that have a significant relationship with the incidence of anemia in pregnant women are maternal education (p value = 0.030), maternal knowledge (p value = 0.005) and economy (p value = 0.0001). The variable of maternal nutritional status (p value = 0.100) did not have a significant relationship with the incidence of anemia in pregnant women at BPM Sri Widayatni. The variable that has the most dominant relationship with the incidence of anemia in pregnant women at BPM Sri Widayatni is economy with a value of OR = 6.554.